Literasi Digital dalam Menangkal Hoax - muhamd ilham setiawan; Muhammad Busyran Abdan Syakuro; Muhammad Fadlan Alkhoir; Nadia Nurdiana (Jurnal Gema Pustakawan, 2025)
In the digital era characterized by the rapid and massive flow of information, society faces a serious challenge in the form of the widespread dissemination of false information or hoaxes. This condition demands an increase in digital literacy as a fundamental ability for individuals to filter, evaluate, and use information wisely. This study aims to analyze the role of digital literacy in countering the spread of hoaxes, particularly among active social media users. The method used is a literature review with a descriptive qualitative approach based on various secondary data sources such as scientific articles, research reports, and official data. The results show that digital literacy which includes the ability to understand sources of information, recognize the characteristics of hoaxes, and think critically about digital content is highly effective in reducing the negative impact of false information. Furthermore, early digital literacy education, training for teachers and educators, and public campaigns by the government and civil society organizations are essential strategies in building society’s information resilience. This study recommends the integration of digital literacy into formal and non-formal education curricula to create a society that is resilient to hoaxes and capable of participating responsibly in the digital space.